Developments in Current Game-Based Learning Design and Deployment 2012
DOI: 10.4018/978-1-4666-1864-0.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Mobile Games for Place-Based Language Learning

Abstract: This paper builds on the emerging body of research aimed at exploring the educational potential of mobile technologies, specifically, how to leverage place-based, augmented reality mobile games for language learning. Mentira is the first place-based, augmented reality mobile game for learning Spanish in a local neighborhood in the Southwestern United States. This paper explores both the complexities and benefits of integrating mobile games in second and foreign language learning contexts. Relevant background i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 18 publications
1
53
0
2
Order By: Relevance
“…Estos estudios prácticos, realizados por diferentes instituciones académicas como el MIT o Harvard, hacen hincapié en la idea de que los juegos en Realidad Aumentada fomentan la capacidad del estudiante, a través de la aventura, para relacionarse con el entorno de modo más interactivo e inmersivo (Klopfer y Squire, 2008;Dunleavy y Dede, 2014), gracias a la información amplificada con aplicaciones de RA. En estas narrativas digitales en forma de juego, los alumnos desarrollan sus habilidades para descubrir, contextualizar e integrar la información por medio de la tecnología móvil, combinando lo virtual y lo real, en un espacio que se extiende más allá del aula (Holden y Sykes, 2011). Para acabar este repaso, destacaremos la relación entre la Realidad Aumentada y los libros.…”
Section: Javier Sánchez Boladounclassified
“…Estos estudios prácticos, realizados por diferentes instituciones académicas como el MIT o Harvard, hacen hincapié en la idea de que los juegos en Realidad Aumentada fomentan la capacidad del estudiante, a través de la aventura, para relacionarse con el entorno de modo más interactivo e inmersivo (Klopfer y Squire, 2008;Dunleavy y Dede, 2014), gracias a la información amplificada con aplicaciones de RA. En estas narrativas digitales en forma de juego, los alumnos desarrollan sus habilidades para descubrir, contextualizar e integrar la información por medio de la tecnología móvil, combinando lo virtual y lo real, en un espacio que se extiende más allá del aula (Holden y Sykes, 2011). Para acabar este repaso, destacaremos la relación entre la Realidad Aumentada y los libros.…”
Section: Javier Sánchez Boladounclassified
“…The ARIS platform [35] offers the possibility to author location-based mobile games. While ARIS has been successfully used in several application examples [36], it does not support multi-player/multi-role games. QuestInSitu is a mobile learning platform including authoring which mainly focuses on assessment [37] by putting them into location-based contexts.…”
Section: Technologymentioning
confidence: 99%
“…Other individual differences such as L2 speaking anxiety may decrease through the use of gamified language learning apps (e.g., [11]), while willingness to engage in a task may increase [12]. Additionally, McCarty et al [10] found that mobile devices may be more effective at holding students' attention than tasks completed on a computer, as students are not as likely to multitask; for example, completing a task on a computer allows students to easily switch between windows or tabs, whereas an app covers the entire screen of a mobile device.…”
Section: Teacher-designed Mobile-assisted Language-learning Materialsmentioning
confidence: 99%